Step
*
2
2
1
1
1
1
of Lemma
cubical-pi_wf
.....antecedent..... 
1. X : CubicalSet
2. A : {X ⊢ _}
3. B : {X.A ⊢ _}
4. I : Cname List
5. J : Cname List
6. K : Cname List
7. f : name-morph(I;J)
8. g : name-morph(J;K)
9. a : X(I)
10. u : J:(Cname List) ⟶ f:name-morph(I;J) ⟶ u:A(f(a)) ⟶ B((f(a);u))
11. ∀J,K:Cname List. ∀f:name-morph(I;J). ∀g:name-morph(J;K). ∀u@0:A(f(a)).
      ((u J f u@0 (f(a);u@0) g) = (u K (f o g) (u@0 f(a) g)) ∈ B(g((f(a);u@0))))
12. H : Cname List
13. L : Cname List
14. h : name-morph(K;H)
15. j : name-morph(H;L)
16. b : A(h((f o g)(a)))
17. (u H ((f o g) o h) b (((f o g) o h)(a);b) j)
= (u L (((f o g) o h) o j) (b ((f o g) o h)(a) j))
∈ B(j((((f o g) o h)(a);b)))
⊢ True
BY
{ ((Assert ⌜((f o g) o h)(a) = h((f o g)(a)) ∈ X(H)⌝ ⋅ THENA Auto)
   THEN (Assert ⌜((f o g) o (h o j)) = (((f o g) o h) o j) ∈ name-morph(I;L)⌝⋅ THENA Auto)
   ) }
1
1. X : CubicalSet
2. A : {X ⊢ _}
3. B : {X.A ⊢ _}
4. I : Cname List
5. J : Cname List
6. K : Cname List
7. f : name-morph(I;J)
8. g : name-morph(J;K)
9. a : X(I)
10. u : J:(Cname List) ⟶ f:name-morph(I;J) ⟶ u:A(f(a)) ⟶ B((f(a);u))
11. ∀J,K:Cname List. ∀f:name-morph(I;J). ∀g:name-morph(J;K). ∀u@0:A(f(a)).
      ((u J f u@0 (f(a);u@0) g) = (u K (f o g) (u@0 f(a) g)) ∈ B(g((f(a);u@0))))
12. H : Cname List
13. L : Cname List
14. h : name-morph(K;H)
15. j : name-morph(H;L)
16. b : A(h((f o g)(a)))
17. (u H ((f o g) o h) b (((f o g) o h)(a);b) j)
= (u L (((f o g) o h) o j) (b ((f o g) o h)(a) j))
∈ B(j((((f o g) o h)(a);b)))
18. ((f o g) o h)(a) = h((f o g)(a)) ∈ X(H)
19. ((f o g) o (h o j)) = (((f o g) o h) o j) ∈ name-morph(I;L)
⊢ True
Latex:
Latex:
.....antecedent..... 
1.  X  :  CubicalSet
2.  A  :  \{X  \mvdash{}  \_\}
3.  B  :  \{X.A  \mvdash{}  \_\}
4.  I  :  Cname  List
5.  J  :  Cname  List
6.  K  :  Cname  List
7.  f  :  name-morph(I;J)
8.  g  :  name-morph(J;K)
9.  a  :  X(I)
10.  u  :  J:(Cname  List)  {}\mrightarrow{}  f:name-morph(I;J)  {}\mrightarrow{}  u:A(f(a))  {}\mrightarrow{}  B((f(a);u))
11.  \mforall{}J,K:Cname  List.  \mforall{}f:name-morph(I;J).  \mforall{}g:name-morph(J;K).  \mforall{}u@0:A(f(a)).
            ((u  J  f  u@0  (f(a);u@0)  g)  =  (u  K  (f  o  g)  (u@0  f(a)  g)))
12.  H  :  Cname  List
13.  L  :  Cname  List
14.  h  :  name-morph(K;H)
15.  j  :  name-morph(H;L)
16.  b  :  A(h((f  o  g)(a)))
17.  (u  H  ((f  o  g)  o  h)  b  (((f  o  g)  o  h)(a);b)  j)  =  (u  L  (((f  o  g)  o  h)  o  j)  (b  ((f  o  g)  o  h)(a)  j))
\mvdash{}  True
By
Latex:
((Assert  \mkleeneopen{}((f  o  g)  o  h)(a)  =  h((f  o  g)(a))\mkleeneclose{}  \mcdot{}  THENA  Auto)
  THEN  (Assert  \mkleeneopen{}((f  o  g)  o  (h  o  j))  =  (((f  o  g)  o  h)  o  j)\mkleeneclose{}\mcdot{}  THENA  Auto)
  )
Home
Index